Perceived risk and intention to use internet banking: The effects of self-confidence and risk acceptance. Issue 2 (3rd April 2018) - Marafon, Daiane Lampugnani; Basso, Kenny; Espartel, Lélis Balestrin; de Barcellos, Márcia Dutra; Rech, Eduardo
Abstract : Purpose: The purpose of this paper is to analyze the moderating role of self-confidence and risk acceptance on the relationship between perceived risk and intention to use internet banking. Design/methodology/approach: A survey was conducted with 180 Brazilian banking customers. The Johnson-Neyman test was used to verify the moderation and significant regions along self-confidence and risk acceptance levels. Findings: Self-confidence and risk acceptance moderate the relationship between risk perception and intention to use internet banking. For individuals with high self-confidence, the effect of perceived risk on intention to use internet banking is lower than it is for individuals with low self-confidence. In the same way, for individuals with high risk acceptance, the effect of perceived risk on intention to use internet banking is lower than it is for individuals with low risk acceptance. Research limitations/implications: This research contributes to the understanding of the conditions (two personal factors) under which risk perception does not influence intention to use a technological tool. Practical implications: This paper provides insights for marketing managers to encourage customers to develop greater risk acceptance and self-confidence to minimize the negative effects of perceived risk of the adoption of internet banking. Originality/value: Although risk perception can contribute to customers' avoidance of internet banking, this is the first paper to verify how acceptance of risk and self-confidence can moderate the effects of perceived risk on intention to use internet banking.